Caribbean reader on development - Wedderburn, Judith, ed. (Friedrich Ebert Stiftung KingstonJA, 1986)
Analyses various development themes with a view to promoting a theoretical understanding of the socio-economic characteristics of Caribbean society. Themes include culture, socialist transformation,the IMF, rural development, labour, women, and the state.